PEMANFAATAN TEPUNG AMPAS KELAPA TERFERMENTASI SEBAGAI CAMPURAN PAKAN IKAN LELE (Clarias gariepinus) - Dewi Merdekawati; Beryaldi Agam; Maryono Maryono (JURNAL MINA SAINS, 2023)
Feed is an important factor in fish farming, where approximately 60% of the production costs are concentrated for feed. Therefore, we need alternative ingredients that can be mixed with feed to reduce the cost of buying feed. Coconut dregs is an alternative source of vegetable protein derived from agricultural waste which can be used as a raw material for fish feed through the flouring process. This study aimed to determine the effect of fermented coconut dregs flour pellet feed as a source of raw feed material on catfish growth. The method used in this study was an experimental method consisting of 5 treatments Treatment A0 (0% fermented coconut dregs flour), treatment A1 (6% fermented coconut dregs flour), treatment A2 (12% fermented coconut dregs flour), A3 (18 % fermented coconut dregs flour), A4 (24% fermented coconut dregs flour). Data were analyzed using variance (ANOVA) with the SPSS application. The results showed that A3 (18% fermented coconut dregs flour) was the best treatment and affected the absolute growth of 9 g, whereas A0 treatment (0% fermented coconut dregs flour) showed the lowest absolute growth of 4 g. The local feed formulations obtained in this study can be used as alternatives to artificial feed.